Sarah Durham y el dolor del amor en Love, Again de Doris Lessing. Sarah Dirham and love ‘s pain in Doris Lessing’s Love, Again - García Navarro, Carmen (Estudios Ingleses de la Universidad Complutense, 2003)
This essay offers a study on ageing and old age as literary matter of Doris Lessings Love, Again (1995). Lessinq aims to investigate the topic through the novels protagonist, an elderly woman who faces the process of ageing in a key moment of her life span: the encounter with love, again. I shall analyze the representation of the old age pattern in one of the last works of Lessings narrative fiction from a perspective which suggests, on the one hand, the need to accept that which has been given to the individual to experiment in his/her life and, on the other hand, the need so subvert certain social and cultural imposed limits. The author’s vision on the contemporary individual, pervaded with a serene pessimism, reveals her compassion for the human being and her interest to approach the many sides of the human codition.